Validation of inertial measurement units for tracking 100m sprint data - Parrington, L.; Phillips, E.; Wong, A.; Finch, M.; Wain, E.; MacMahon, C. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Wearable micro sensor measurement devices are a promising development in sports technology. This paper presents preliminary data evaluating the accuracy of an inertial measurement unit during 100m sprints against a criterion measure from a tripod-mounted Laveg laser. The inertial measurement units were found to be a valid tool for the analysis of peak velocity (r = 0.92) and average split velocities for splits after the first 10m (r = 0.85 - 0.95). Validation data suggests some caution should be taken in interpretation of the first lorn split (r = 0.32). Whilst data from the two devices for this split were correlated, the inertial measurement unit showed an overestimation for this parameter in comparison to the athlete velocity as measured by the laser. Further in-depth analysis should investigate this period.